Integrated Problem Based Learning (PBL) Evaluation by Students in Kerbala Medical College - Al Jobori, Shahrazad S; Al Mousawi, Ali M; Abutiheen, Ali A. (AL-Kindy College Medical Journal, 2016)
Background: Scientific education aims to be inclusive and to improve students learning achievements, through appropriate teaching and learning. Problem Based Learning (PBL) system, a student centered method, started in the second half of the previous century and is expanding progressively, organizes learning around problems and students learn about a subject through the experience of solving these problems.Objectives:To assess the opinions of undergraduate medical students regarding learning outcomes of PBL in small group teaching and to explore their views about the role of tutors and methods of evaluation. Type of the study: A cross-sectional study.Methods: This study was conducted in Kerbala Medical Colleges among second year students. A self-administered questionnaire was prepared to evaluate the newly applied teaching system. The study analysis included simple descriptive analysis and determining association through t-test, chi square test and regression analysis and using structural equation models to determine simultaneous association between different students’ demographic characteristics and potential predictors using SPSS-20 and Amos software at a significance level of < 0.05.Results:A total of 131 undergraduate medical students participated in the study with a response rate of 94%. The majority (93%) have indicated that PBL strategy contributed effectively to their knowledge development with a similar majority (92%) considering PBL successful new teaching method. About 86% reported that would choose PBL rather than conventional method and also 86% would advise PBL for others. Similarly, high majority indicated that various PBL activities are essential. Regarding the tutors’ role in PBL, the majority (92%) indicated that this role was positive and fundamental. According to two thirds (68%) of participants PBL application in Kerbala Medical college was very good application while a higher majority described various PBL sessions as successful and positive and fundamental role of tutors was stressed by most students.Conclusions: This study highlighted the benefits of soliciting student impressions of effective small group teaching. The students’ emphasized group atmosphere and facilitation skills of tutor in learning.Key words: Problem Based Learning, Medical Education, Small Group Teaching, Team Based Learning, Kerbala Medical College